2012
DOI: 10.1111/j.1365-3164.2012.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear survivin expression as a potentially useful tool for the diagnosis of canine cutaneous sebaceous lesions

Abstract: The level of survivin expression increased with increasing malignancy, designating survivin as a new diagnostic marker in the assessment of malignancy of sebaceous tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
1
15
1
Order By: Relevance
“…Bongiovanni et al () have determined that the immunolabeling of survivin and Ki67 is overlapped in canine epidermis, hair follicles and sebaceous glands (Bongiovanni et al, ). Recently, Bongiovanni et al () have found that survivin is expressed only in scattered reserve cells of normal sebaceous glands, where stem cells are supposed to reside. These authors have hypothesized that survivin could represent a marker for “sebaceous” stem cells or progenitor cells and they have suggested that survivin could possibly play a similar prosurvival role in sebocytes as in keratinocytes, guaranteeing the long life of stem cells in their niche (Bongiovanni et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Bongiovanni et al () have determined that the immunolabeling of survivin and Ki67 is overlapped in canine epidermis, hair follicles and sebaceous glands (Bongiovanni et al, ). Recently, Bongiovanni et al () have found that survivin is expressed only in scattered reserve cells of normal sebaceous glands, where stem cells are supposed to reside. These authors have hypothesized that survivin could represent a marker for “sebaceous” stem cells or progenitor cells and they have suggested that survivin could possibly play a similar prosurvival role in sebocytes as in keratinocytes, guaranteeing the long life of stem cells in their niche (Bongiovanni et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…MI and PI assessed as the number of mitotic figures and the percentage of Ki67-positive cells, respectively. According to our knowledge only a few such studies have been previously conducted on canine osteosarcomas (Bongiovanni et al 2012a, Davies et al 2012, Shoeneman et al 2012) and sebaceous lesions (Bongiovanni et al 2012b) and has not been previously reported in canine NHLs.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies have revealed expression of this protein in some canine tumors including transitional cell carcinomas of urinary bladder (Rankin et al 2008), cutaneous tumors (Bongiovanni et al 2009(Bongiovanni et al , 2012b and osteosarcomas (Bongiovanni et al 2012a, Davies et al 2012, Shoeneman et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Schematic illustration of survivin expression patterns in skin structures during the various stages of the canine hair follicle cycle. The interfollicular epidermal and sebaceous gland data for Ki67 and survivin are derived from Bongiovanni et al3,11 Immunofluorescence in normal hair follicles. First column shows blue nuclei with 4′,6-diamidino-2-phenylindole counterstain.…”
mentioning
confidence: 99%